Dual antiplatelet therapy challenges in emergent noncardiac surgeries - Rahil Singh (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2021)
In today's era, patients with coronary stents are presenting for various surgeries while still being on dual antiplatelet therapy. This leads to balancing the risk between myocardial ischemia if therapy is discontinued and bleeding risk due to surgery. Hence, it arises the need to introduce guidelines for managing such patients coming for elective as well as emergency surgeries for easy implementation. Developments related to coronary stents and antiplatelet agents are continuously evolving. A comprehensive understanding of the pharmacology of newer antiplatelet agents, efficacies of newer coronary stents, risk of stent thrombosis, and role of platelet function tests must be determined. There is an urgent need for the development of guidelines to manage such patients.